(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Stunting malnutrition is an indicator of chronic malnutrition, reflecting the results of a long process of caring and nourishing undernourished children. Objectives: (1) Determine the proportion of stunted malnutrition among primary school students in the coastal area of Phu Vang district, Thua Thien Hue province, and (2) explore some related factors. Method: A cross-sectional descriptive study, was performed on 417 students in non-boarding primary schools and their mothers. Results: 7.0% of students suffering from stunting malnutrition, in which the prevalence of stunting at medium and severe levels were 6.0% and 1.0%, respectively. There were statistically significant relationships between the stunting status with housing type factors, milk used by students, diagnosis of malnutrition in the past year and father’s height (p<0.05). Conclusion: The percentage of stunting malnutrition among primary school students was still high. The health sector should make practical plans and implement a variety of measures to improve the nutritional status of students.